Professional counselors’ preventive approach to students’ social anxiety through sociodrama-based group guidance - Nazalia Febrina Fasya Abidin; Khairul Barriyah (Journal of Professional Teacher Education, 2026)
Social anxiety is a common problem among high school students and can hinder both social and academic development. Therefore, preventive measures are needed to stop social anxiety from escalating into a more severe condition. This study aims to test the effectiveness of group guidance services using sociodrama techniques as a preventive measure against the development of social anxiety among students at SMAN 5 Malang, a public Senior High School in Malang, Indonesia. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The study sample consisted of eight students with moderate to high levels of social anxiety, selected using purposive sampling. Data were collected using a social anxiety scale that met validity and reliability criteria. Group guidance sessions using sociodrama techniques were conducted over four meetings, followed by a posttest to assess changes in the students’ social anxiety levels. Hypothesis testing was performed using the Wilcoxon Signed-Rank Test, with the results showing a significance value of 0.012 (< 0.05), indicating a significant difference between the pretest and posttest scores. These findings suggest that group guidance services using sociodrama techniques have the potential to support preventive measures by reducing students’ levels of social anxiety. Consequently, they can be utilized as a preventive strategy to stop social anxiety from developing into a more severe condition and to help students develop social skills and self-confidence in social situations.